CRIAÇÃO DE PROBLEMAS: CONTRIBUIÇÕES PARA A PROPOSIÇÃO DE ITINERÁRIOS FORMATIVOS PARA O ENSINO MÉDIO - Machado, Thaís de Souza (2024)
The present research is linked to the research line Teaching and Learning of Science and Mathematics within the Academic Master's program in Science and Mathematics Education at Universidade Franciscana. It focuses on proposing a research project aimed at Mathematics teaching and learning using Formative Pathways with 3rd-year High School classes in the state of Rio Grande do Sul. The research aims to investigate the contributions that Problem Creation, based on everyday contexts, can bring to the formalization of mathematical knowledge through Formative Pathways in High School. The proposed activity was implemented with 12 third-year High School students at a state school located in São Pedro do Sul - RS. Planned actions followed the principles proposed by author Uldarico Malaspina, emphasizing Problem Creation. Data collection involved field diary records of activities and student-generated records. Data analysis was conducted by categorizing the problems and solutions developed by the students. Results indicate that students were able to create problems with mathematical coherence, and that problem creation contributed to fostering students' creativity, autonomy, motivation, and protagonism. It is expected that this activity will become an effective resource to enhance learning and make Mathematics studies more engaging and interesting for students.